THE ROLE OF INTERNAL AUDIT, INTERNAL CONTROL, ORGANIZATIONAL COMMITMENT AND INTEGRITY, IN IMPROVING OPTIMIZATION OF FRAUD PREVENTION AT HOSPITALS IN SIDOARJO - Jena Sarita; Hwihanus Hwihanus; Slamet Riyadi (WORLDVIEW ( Development economic and sharia studies journal ), 2023)
This research aims to determine the influence of internal control, internal audit, organizational commitment and integrity on fraud prevention at Hospital X in Sidoarjo. In this regard, to maximize rational, measurable and in-depth research results, this research uses quantitative methods. The data source in this research is a primary data source obtained from respondents from distributing questionnaires indirectly or utilizing existing communication media. Meanwhile, the sampling technique in the research used a probability sampling technique (single random sampling), namely a certain number of employees at Hospital X in Sidoarjo. Data obtained using a questionnaire processed using SPSS 23 for 43 employees of Hospital X Sidoarjo. So the results obtained are that internal audit has no significant effect on fraud prevention, internal control has a significant effect on fraud prevention, organizational commitment has a significant effect on fraud prevention, and Integrity has a significant effect on fraud prevention at Hospital X Sidoarjo.